In-plane response of masonry infill walls: Comprehensive experimentally-based equivalent strut model for deterministic and probabilistic analysis. (15th July 2018) - Liberatore, Laura; Noto, Fabrizio; Mollaioli, Fabrizio; Franchin, Paolo
Highlights: A data-set is compiled of 162 experimental tests available in the literature. A comparative performance assessment of different strut models is made. A novel constitutive model is calibrated through multivariate regression analyses. The model error terms are characterized in terms of marginals and correlation matrix. An example of application of the proposed model is carried out. Abstract: It is widely recognised that the presence of infills modifies the global structural response of frame buildings subjected to seismic loads. Despite the substantial research carried out in the last decades, the assessment of the seismic performance of infilled frames remains an open issue due to the complexity of the interaction between the infill and the frame and to the large number of parameters involved. In this study, a data set of 162 experimental tests available in the literature is initially employed to assess the reliability of different models based on the equivalent strut approach. The comparison between predicted and experimental values highlights large uncertainties, especially for the stiffness prediction. A novel model is thus developed, that duly takes into account these uncertainties. The constitutive model is piecewise-linear, where characteristic force–displacement points are clearly defined and the related error terms are estimated. Beside the masonry mechanical characteristics, the model considers different features, such as the presence of vertical or horizontal hollows in the units. An example of application of the proposed model is finally presented. Specifically, the cyclic response of experimental tests not included in the original data set is reproduced by making use of the suggested strut model.